Limnochemistry of Three Freshwater Springs of Kashmir Himalaya - Bhat, Sami Ullah; Pandit, Ashok K. (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
The present investigation was carried out during 2005-06 on three limnocrene freshwater springs located in single groundwater area in Kokergund (Yaripora) of District Kulgam, Kashmir, India. A perusal of the data showed that these springs were hard water type with slightly lower values of dissolved oxygen (DO) (1.2-6.4mg/L). The ionic composition of the spring waters revealed the predominance of bicarbonate and calcium over the other ions with usual ionic progression as HCO3- >Ca++ >Mg++ >Na+ >K+. None of the parameters studied foated the standards set by WHO for drinking water quality. However, relatively higher values of NO3-N (2500-3900µg/L), but well within the per-missible limits of WHO, were observed. The dissolved silica did not show any temporal variation between the different months but exhibited slight spatial variations (17.8-21mg/L). Key words: Limn chemistry; Water quality; Groundwater; Kashmir Himalaya DOI: 10.3126/hn.v7i0.4237 Hydro Nepal Journal of Water, Energy and Environment Vol. 7, July, 2010 Page: 54-59 Uploaded date: 31 January, 2011